HETEROTRANSPLANTATION OF BLOOD VESSELS PRESERVED IN COLD STORAGE - Carrel, Alexis (The Rockefeller University Press, 1907)
The experiments show merely that blood vessels transplanted from dog to cat can act as arteries for seventy-seven days at least; and that having spent several days in cold storage does not interfere with their ordinary functions. The animals operated upon must, however, be kept under observation for several months, or, indeed, for several years, before any conclusion can be drawn concerning the practicability of this method of preservation and heterotransplantation of blood vessels.